2019
DOI: 10.1589/jpts.31.633
|View full text |Cite
|
Sign up to set email alerts
|

Improvement and sustainability of walking ability with hybrid assistive limb training in a patient with cerebral palsy after puberty: a case report

Abstract: [Purpose] Cerebral palsy is one of the most common causes of childhood physical disability affecting motor development. Gait training with a wearable-robot, such as the Hybrid Assistive Limb, has been reported to improve gait ability in patients with chronic motor disabilities; however, there are no reports concerning the sustained improvement of walking ability with its use in patients with cerebral palsy. We present our observations for the use of Hybrid Assistive Limb gait training in a postpubescent cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…With the exception of Lerner, Damiano and Bulea [ 32 ] who did not report any change, all the other eight studies found improvements in step length. Four studies [ 41 , 43 45 ] had a statistically significant increase in step length, while three studies [ 31 , 39 , 42 ] did not support their findings with statistical significance. Matsuda et al [ 47 ] found a non-statistically significant increase in step length for both self-selected walking speed (P = 0.078) and maximum walking speed (P = 0.739) in participants using the HAL exoskeleton.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…With the exception of Lerner, Damiano and Bulea [ 32 ] who did not report any change, all the other eight studies found improvements in step length. Four studies [ 41 , 43 45 ] had a statistically significant increase in step length, while three studies [ 31 , 39 , 42 ] did not support their findings with statistical significance. Matsuda et al [ 47 ] found a non-statistically significant increase in step length for both self-selected walking speed (P = 0.078) and maximum walking speed (P = 0.739) in participants using the HAL exoskeleton.…”
Section: Resultsmentioning
confidence: 92%
“…While most of the included studies scored well for criterion two [ 31 – 34 , 39 , 41 48 ] and criterion 14 [ 31 – 34 , 39 , 41 45 , 47 , 48 ], there were a number of methodological concerns. These included measurement bias due to lack of psychometrically sound outcome measures [ 31 33 , 39 , 41 48 ], co-intervention bias [ 31 33 , 39 , 42 , 43 , 47 , 48 ] and lack of appropriate analytical methods [ 31 , 39 , 42 , 48 ]. While the lack of blinding of the participants, therapists and measures increases the risk of placebo, Hawthorne effect and measurement bias, given the nature of the intervention, these biases could not be entirely avoidable.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations